Pengembangan Industri UMKM Batik Khas Kabupaten Malang melalui Digitalisasi Marketing Mix dan Teknologi - Vika Annisa Qurrata; Ermita Yusida; Sudjatmiko Sudjatmiko; Lustina Fajar Prastiwi (University of Merdeka Malang, 2021)
The development of SMEs is still one of the development priorities in Indonesia. One example is the Dewandaru Batik industry in Malang Regency. The business, which was started in 2017 and is engaged in batik cloth production, carries out the production process manually with limited tools. The price that is determined tends to be very cheap compared to batik marketed through the market and online galleries. Moreover, every month's limited production is the impact of the lack of technology used and little marketing. Marketing and utilization of appropriate technology are still the main obstacles faced; therefore, the solution to this problem is digitizing the marketing mix and proper technology. The method used is identifying problem-solving and assistance for increasing industrial innovation and digital marketing. The result of this activity was an increase in Dewandaru's batik industry's productivity with the help of a batik stamp tool and a dipping tub used for the coloring process. Furthermore, increasing quality makes for a broader marketing market. Batik Dewandaru also experienced improvements in business management because it made simple financial reports on the results of business management training.